2017
DOI: 10.1159/000478735
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin Variations and Mortality in Incident Hemodialysis Patients

Abstract: Background: Higher serum ferritin levels may be influenced by iron use and inflammation, and are associated with higher mortality in hemodialysis (HD) patients. We hypothesized that a major rise in serum ferritin is associated with a higher risk of mortality, irrespective of baseline serum ferritin in incident HD patients. Methods: In a cohort of 93,979 incident HD patients between 2007 and 2011, we examined the association of change in serum ferritin from the baseline patient quarter (first 91 days from dialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
(43 reference statements)
1
22
0
1
Order By: Relevance
“…The high-efficiency OL-HDF might already place β 2 M into the lowest level due to the fact that the patients got the maximal survival benefit from effective large molecular toxin clearance. Interestingly, some previous studies also showed the mortality risk of high ferritin in HD patients as in the present study [19-21]. The adverse effects of high iron in the body have been established.…”
Section: Discussionsupporting
confidence: 82%
“…The high-efficiency OL-HDF might already place β 2 M into the lowest level due to the fact that the patients got the maximal survival benefit from effective large molecular toxin clearance. Interestingly, some previous studies also showed the mortality risk of high ferritin in HD patients as in the present study [19-21]. The adverse effects of high iron in the body have been established.…”
Section: Discussionsupporting
confidence: 82%
“…International guidelines for the management of IDA recommend that IV iron should be discontinued when serum ferritin is >1123.5–2696.4 pmol/L [ 3 , 29 ]. However, high levels of CRP [ 6 , 30 ] and serum ferritin of >179.8–1797.6 pmol/L were associated with worse outcome in HD patients [ 14 , 31 , 32 , 33 , 34 ]. In addition, serum ferritin levels of >1123.5–1797.6 pmol/L were associated with high mortality in HD patients in Europe, the U.S. [ 34 , 35 ] and Taiwan [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, high levels of CRP [ 6 , 30 ] and serum ferritin of >179.8–1797.6 pmol/L were associated with worse outcome in HD patients [ 14 , 31 , 32 , 33 , 34 ]. In addition, serum ferritin levels of >1123.5–1797.6 pmol/L were associated with high mortality in HD patients in Europe, the U.S. [ 34 , 35 ] and Taiwan [ 31 ]. In these studies [ 31 , 34 , 35 ], the levels of CRP were high in the majority of the HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inflammation significantly affects upper serum ferritin targets to avoid iron overload for the management of IDA in CKD patients. In support of this hypothesis, in the setting of concomitant inflammation, serum ferritin levels of ≥500–800 ng/mL are found to be predictive of high mortality in HD patients of Europe [ 9 , 101 ] and Taiwan [ 92 ] and USA [ 95 ]. High CRP levels alone may predict high mortality in HD patients [ 62 , 102 ].…”
Section: Ida In Ckdmentioning
confidence: 97%
“…It is controversial whether iron overload is associated with a risk of infection or infection-related mortality [ 91 ]. High serum ferritin has been shown to be an independent risk factor of infection-related mortality in HD patients [ 7 , 92 , 93 , 94 , 95 ]. Bolus dosing of ferric gluconate could increase a risk of infection-related mortality and hospitalization in HD patients with catheter [ 96 ].…”
Section: Ida In Ckdmentioning
confidence: 99%